Digital Monetary Resources of Russia (digital ruble) as a Means of Distribution in the Financial System: Legal Aspects of Possible Application - A. В. Ivanujenko (Теоретическая и прикладная юриспруденция)
The article discusses the legal aspects of digital rubles being introduced into the monetary system of Russia in the near future. The author, analyzing current legislation, existing studies, foreign practice on the introduction of similar monetary units and statements of Russian practitioners in the field of public finance, comes to the conclusion that the introduction of a new type of Russian banknotes is a response to sanctions from the so-called “unfriendly states” that create certain risks for the development of the Russian financial system. The author comes to the conclusion that the digital ruble is the next step towards the development of the principles of targeting, efficiency and the purpose of budget funds. In addition, the author comes to the conclusion that the introduction of the digital ruble contributes to the solution of issues such as the effectiveness of social policy and anti-corruption.